Prevalence of Human Papillomavirus (HPV) and Other Sexually Transmitted Infections (STIs) among Italian Women Referred for a Colposcopy - Martinelli, Marianna (Int J Environ Res Public Health, 2019)
Sexually transmitted infections (STIs) represent a major cause of morbidity in women and men worldwide. Human Papillomavirus (HPV) infections are among the most prevalent STIs and persistent infections with high-risk HPV (hrHPV) genotypes can cause cervical dysplasia and invasive cervical cancer. The association of other STIs with HPV cervical infection and/or dysplasia has however not yet been fully elucidated. The aim of this study was to assess the prevalence of HPV and other STIs among women presenting with an abnormal cervical cytology. Cervical infections with 28 HPV genotypes and seven other sexually transmitted pathogens were evaluated in 177 women referred for a colposcopy after an abnormal Pap smear. Positivity for at least one hrHPV genotype was shown in 87% of women; HPV 16 was the most prevalent (25.0%), followed by HPV 31 and HPV 51. The overall positivity for other STIs was 49.2%, with Ureaplasma parvum being the most prevalent microrganism (39.0%). Co-infections between hrHPV and other STIs were demonstrated in 17.5% of women; no significant association was demonstrated between multiple infections and the colposcopy findings. This study provides new epidemiological data on the prevalence of cervical infections associated with HPV and seven other common sexually transmitted pathogens in a population of women presenting with an abnormal cervical cytology.